Dependencies Spatial Economic and Employment Indicators in East Java - Prihadyatama, Ardila; Nugroho, Sasmito Widi; Kurniawan, Handika Asep; Haning, Nastadia Nikmatul Wagita (Eastasouth Institute, 2024)
This study investigates the spatial dynamics of economic growth in East Java Province by applying spatial panel econometrics models. Using secondary panel data from 38 districts/cities for the period 2016–2023, the research incorporates variables such as economic growth rate, regional original income (PAD), capital expenditure, and labor. The Moran’s I test reveals a negative value, indicating spatial dispersion patterns where high-growth regions are surrounded by low-growth areas and vice versa, suggesting regional inequality. Furthermore, the Spatial Autoregressive (SAR) model confirms the existence of significant inter-regional spillover effects, meaning that economic growth in one region can positively influence neighboring areas. The Spatial Error Model (SEM) also highlights the role of unobserved external factors such as geography, institutions, and socio-cultural aspects. Empirical findings show that PAD and capital expenditure have a significant positive impact on economic growth, while labor does not significantly affect regional development outcomes, emphasizing the importance of workforce quality over quantity. These results underline the necessity of collaborative and inclusive development planning, fiscal strengthening, and strategic investment in human resources to reduce interregional disparities and promote sustainable growth across East Java.